The Body of Property : Antebellum American Fiction and the Phenomenology of Possession - Luck, Chad (Book collections on Project MUSE., 2014)
"Explores the embodied aspects of ownership and private property as these emerge in a range of American literary texts across the late eighteenth and early nineteenth century"--